Application of the An-Nahdliyah Method in Improving Maharoh Qiro’ah Skills in Learning al-Qur’an at the Roudlotut Tholibin Islamic Bording School | Penerapan Metode An-Nahdliyah dalam Meningkatkan Keterampilan Maharoh Qiro’ah pada Pembelajaran al-Qur’an di Pondok Pesantren Roudlotut Tholibin - Nurul Hasanah; Nafi’atur Rohmah; Anjarwati; Faedurrohman (An-nahdloh : Journal of Arabic Teaching, 2023)
This study presents the Application of the An-Nahdiyah Method in Improving Maharah Qiro'ah Skills in Learning the Qur’an at the Roudlotut Tholibin Islamic Boarding School. Teaching can be done in various ways, one of which is with existing guidelines. The method is very important as a guide for educational goals to be achieved. One of them is the An-Nahdliyah method which can improve Maharoh Qiro'ah in Arabic. Humans today are not enough to use intellectual and spiritual intelligence, they must also be equipped with basic social intelligence. In this research, the solution to this problem is how the application of the An-Nahdliyah Method at the Roudlotut Tholibin Islamic Boarding School can improve Maharah Qiro'ah in accordance with the objectives of learning Arabic. This study uses a descriptive qualitative approach through observation, interviews, and documents. The results showed that the learning activities of the An-Nahdliyah Method at the Roudlotut Tholibin Islamic Boarding School were used traditionally with the same learning material, namely the suitability and regularity of reading by using a beat or murotal footbridge as a tool. The An-Nahdliyah method was studied in early classes before Awaluma as a way to make early-level students able to learn and make reading the Qur'an and Arabic easier.